SIRT2 as a Therapeutic Target for Age-Related Disorders - Machado de Oliveira, RIta; Sarkander, Jana; Kazantsev, Aleksey G.; Outeiro, Tiago F. (Frontiers in Pharmacology, 2012)
Sirtuin proteins are conserved regulators of aging that have recently emerged as important modifiers of several diseases which commonly occur later in life, such as cancer, diabetes, cardiovascular and neurodegenerative diseases. In mammals, there are seven sirtuins (SIRT1-7), which display diversity in subcellular localization and function. SIRT1 has received much of attention due to its possible impact on longevity, while important biological and therapeutic roles of other sirtuins have been underestimated and just recently recognized. Here we focus on SIRT2, a member of the sirtuin family, and discuss its role in cellular and tissue-specific functions. This review summarizes the main scientific advances on SIRT2 protein biology and explores its potential as a therapeutic target for treatment of age-related disorders.